TECHNOLOGIES OF PEDAGOGICAL AND PSYCHOLOGICAL APPROACH TO EDUCATION OUTSIDE SCHOOL - Pulatova Dildora Turgunovna (American Journals, 2023)
This article discusses in detail the system of extracurricular education, the educational process in it, the content of circles, content issues. The process of familiarization with the involvement of children in circles, their abilities and talents that develop in circles, the latest achievements of modern professions and methods revealed the content of the article in pedagogical and psychological terms.
Keywords: extracurricular education, children, talent, process, profession, success, content.